Plan de negocios para la creación de una empresa de asesorías y consultoras integrales en Buenaventura (2013)
This Graduation Project is a business plan for the creation of a business advisory services and PosiblExpress Integral Consulting Ltd., it aims at private companies inthes e city of Buenaventura, in order to advise on the creation and establishment of organizations, support to stay in the market, support and internal financial and social growth of the same, and their partners and family thus, contribute to economic growth of the country. It arises from the need to provide assistance to commercial enterprises, customs, port, and financial services, with a portfolio of services based on the main shortcomings identified by the indicators, which resulted from information provided by customers/ users, which through a diagnostic analysis that allows to know what is happening inside these so that it can take the appropriate preventive and corrective actions. In the portfolio of services offered to clients, specialized in issues such as: Customs and Port Management, Development and Human Resources, Customer Service, Accounting, Financial Analysis and Growth, Marketing and Information Technology, was taken into account Research, development and Innovation I + D + I, as a strategic pillar are reflected in the development of methodologies for the implementation of solutions in each area of companies with different economic activities within the national and international standards related to best practices in information and knowledge management. As Porter (1991) and Marshall described the theory of the business environment, how the growth of a company is subject to the environment in which it finds itself in the same way, with PosiblExpress Ltda. a considerable economic growth is projected for all stakeholders. Finally, the implementation of this Integrated Advisory and Consulting services company, will be able to respond to the administrative, operational and production needs for the effective targeting of private companies with solutions according to their sizes at affordable prices, while offering these, updated, timely, dynamic, objective and understandable training information, just in time, to analyze and make sound decisions and correct at the right time, and always projected towards the global, sustainable and socially responsible.